The Effect of Workload and Musculoskeletal Complaints on Nurse Performance at Pirngadi Hospital, Medan City - Rina Rahmadani; Lilis Pujiati (TOUR HEALTH JOURNAL, 2022)
This research aims to determine the effect of body mass index and workload on fatigue and musculoskeletal disorders and their impact on nurse performance. The type of this research was quantitative research with cross sectional method. The research sample used proportional random sampling method as many as 103 respondents to describe the effect of body mass index and workload on fatigue and musculoskeletal disorders and their impact on performance, data were analyzed by using Pearson correlation and path analysis. The results showed that BMI variables had no effect on work fatigue (p = 0.886), BMI variables had no effect on performance (p = 0.789), workload variables had an effect on musculoskeletal disorders complaints (p = 0.019), workload variables had an effect on performance ( p = 0.004), work exhaustion variables had an effect on performance (p = 0.016), variable musculoskeletal disorders complaints had an effect on performance (p = 0.023). The results of path analysis showed the effect of workload on musculoskeletal disorders complaints on the performance of nurses hospitalization was -0,314 and the effect of body mass index on work fatigue and its impact on the performance of nurses hospitalized was 0.027.